Herbal Formula Longteng Decoction Promotes the Regression of Synovial Inflammation in Collagen-Induced Arthritis Mice by Regulating Type 2 Innate Lymphocytes - Huijie Zhang; Juan Liu; Pingxin Zhang; Dongyang Li; Guiyu Feng; Meiyier Huandike; Song Sun; Limin Chai; Jingwei Zhou; Jingwei Zhou (Frontiers Media S.A., 2021)
The etiology and pathogenesis of rheumatoid arthritis (RA) have not yet been fully elucidated, with greater adverse drug effects in traditional treatment of RA. It is particularly necessary to develop and study Chinese herbal formula as a supplement and alternative drug for the treatment of RA. The traditional Chinese medicine compound Longteng Decoction (LTD), as an empirical prescription in the treatment of RA in Dongzhimen Hospital of Beijing University of Chinese Medicine, has been widely used in clinic. Type 2 innate lymphocytes (ILC2s) have specific transcription factors and signature cytokines that are very similar to Th cells, which have been proved to be necessary in addressing RA inflammation, and are potential targets for RA prevention and treatment. Our previous studies have confirmed that LTD can intervene in the differentiation of peripheral blood Th17 and Treg cells, reduce joint pain index and swelling degree, shorten the time of morning stiffness, reduce ESR, and inhibit joint inflammation. However, it is unclear whether LTD can promote the regression of RA synovial inflammation by regulating the immune response mechanism of ILC2s.Therefore, our team established a collagen-induced arthritis mouse model and conducted an experimental study with LTD as the intervention object. The results showed that joint swelling, synovial inflammatory infiltration, and articular cartilage destruction were alleviated in CIA mice after intervention with LTD. The proliferation and differentiation of Th17 inflammatory cells and the secretion of proinflammatory cytokines (IL-17 and IFN-γ) were inhibited. In addition, LTD can also activate ILC2s to secrete the anti-inflammatory cytokine IL-4, activate the STAT6 signaling pathway, and act synergistic with Treg cells to inhibit the infiltration of type M1 macrophages in synovial tissue and promote its transformation to M2 phenotype. Taken together, these results confirm that LTD can be used as an adjunct or alternative to RA therapy by modulating the ILC2s immune response network and slowing down the inflammatory process of synovial tissue.